THE CONCEPTION OF NEOCLASSISIZM IN VOLODYMYR DERZHAVYN LITERARY INHERITANCE - Basenko, N. V. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Word, 2021)
The attempt of complete scientific analysis of the conception of neoclassisizm in Derzhavyn literary studies is realized in the article. The main conseptial positions and methodological principles of determination of neoclassisizm as literary style are shown.